Increasing the social participation of older rural residents: Opportunities offered by "OPTEACH". (28th June 2019) - Hughes, Clarissa; Bernoth, Maree; Winkler, Denise
Abstract: Problem: The issues addressed in this article are two‐fold. Firstly, education about ageing is predominantly textbook‐based. Secondly, many rural older people face social isolation which impacts their health. In addressing the first issue, we discovered that our project, Older Persons Teaching and Empowering Aged Care Students (OPTEACH), has the potential to have a positive impact on the second issue. Design: We run university education sessions involving older people. Since such sessions present unique challenges, we obtained a grant to develop resources to assist educators and support rural older people to become "OPTEACHers." Setting: OPTEACH was undertaken in several rural communities in New South Wales and included staff and residents at residential aged care facilities and community‐dwelling rural older people. Key measures for improvement: Our previous work had highlighted a need for educator resources that would facilitate "ageing" being taught in a way that both involved and respected older people. Our ethos centres on the "co‐creation" of knowledge, and having older peoples' unique contributions recognised and celebrated. Strategies for change: Resources to assist with planning and being involved in OPTEACH education sessions are available atwww.opteach.com.au . They will support a growing community of "OPTEACHers, " with beneficial flow‐on effects for rural older people. Effects of change: We seek to provide practical support to both educators and older people to provide "real life" education on the experience of ageing. Next steps: Further evaluation is needed, yet we anticipate a positive impact on self‐esteem, community "connectedness" and quality of life for older rural "OPTEACHers" as the approach gains momentum.